The natural compound magnolol affects growth, biofilm formation, and ultrastructure of oral Candida isolates. (December 2017) - Behbehani, Jawad; Shreaz, Sheikh; Irshad, Mohammad; Karched, Maribassapa
Abstract: The incidence of oral candidosis has increased in recent years due to the escalation in HIV-infection, cancer treatments, organ transplantation, and diabetes. In addition, corticosteroid use, dentures, and broad-spectrum antibiotic use have also contributed to the problem. Treatment of oral candidosis has continued to be problematic because of the potential toxicity of antifungals in clinical use, and, above all, development of drug resistance among patients. In this study, the antifungal effect of magnolol was investigated against 64 strains of Candida spp. (four standard and 60 oral isolates) through minimum inhibitory concentration (MIC) and growth curve assays. Insight into the mechanisms of the antifungal action has been gained through ultrastructural studies using confocal scanning laser microscopy (CSLM), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Molecular docking was done for predicting the interactions of magnolol with ergosterol at supramolecular level. The toxicity of magnolol on human erythrocytes was measured by in vitro hemolytic assay. MIC values of magnolol ranged from 16-64 μg/ml, respectively. All tested isolates showed a marked sensitivity towards magnolol in growth curve assays. Biofilm results suggested that magnolol showed strong anti-biofilm activity. The results obtained for four different Candida spp. demonstrated that MBIC values of magnolol showed the average biofilm inhibition by 69.5%, respectively. CLSM experiments showed that cells exposed to magnolol (MIC) exhibited cell membrane disruption. SEM analysis of magnolol treated cells resulted in deformed cells. TEM micrographs showed rupturing of the cell wall and plasma membrane, releasing the intracellular content, and swelling of the cell wall. Hemolytic activity of magnolol is 11.9% at its highest MIC compared to an activity level of 25.4% shown by amphotericin B (Amp B) at 1 μg/ml. Lipinski's parameters calculated for magnolol suggested its good oral bioavailability. Docking studies indicated that magnolol might be interacting with ergosterol in the fungal cell membranes. Together, the present study provides enough evidence for further work on magnolol so that better strategies could be employed to treat oral candidosis. Graphical abstract: Highlights: Magnolol shows anticandidal activity in the concentration range of 16–64 µg/ml. Biofilm results suggested that magnolol shows significant anti-biofilm activity. Microcopy results showed that exposure to magnolol resulted in deformed cells and cell membrane disruption. Lipinski's parameters calculated for magnolol suggested its good oral bioavailability. Docking studies indicated that magnolol might be interacting with fungal ergosterol.